Educational tourism as an economic category and a tool for increasing the competitiveness of the tourism industry: conceptual framework and classification - Mamrayeva, D.G.; Tashenova, L.V. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: The object of research is the essence and content of educational tourism. Methods: Bibliographic analysis and classification method. Results: The article studies the approach to the definition of “educational tourism”, including economic, activity, program-oriented, need-oriented, and combined. Based on the bibliographic analysis in the scientometric database Web of Science, an array of publications was studied and key scientific directions on the scientific problem under considera-tion were identified. The existing classification of educational tourism is given. The author’s definition of the concept of “educational tourism” is given and classification of the types of educational tourism is obtained based on the distin-guished features of the grouping. Conclusions: At present, there is still no single approach to the definition and classification of educational tourism due to its interdisciplinarity, characterized by the relationship of economic, pedagogical, geographical, historical, be-havioral, and many other sciences. Within the framework of this scientific article, we have identified 16 classification features of educational tourism, given the authors’ definition, including aspects of digitalization, which have become an integral component of the modern process of learning and cognition.
Білім беру туризмі экономикалық категория және туристік саланың бәсекеге қабілеттілігін арттыру құралы ретінде: тұжырымдамалық негіздер және жіктелуі
Образовательный туризм как экономическая категория и инструмент повышения конкуренто-способности туристской отрасли: концептуальные основы и классификация
Keywords: educational tourism; bibliographic analysis; approaches to definition; classification and types; compo-nents of educational tourism